ISOLASI DAN KARAKTERISASI FUNGI ENDOFIT DARI KULIT BUAH MANGGIS (Garcinia mangostana L) SEBAGAI ANTIMIKROBA TERHADAP Candida albicans, Staphylococcus aureus DAN Escherichia coli - Dewi Elfina; Atria Martina; Rodesia Mustika Roza (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Garcinia mangostana Linn is one of the popular local plants that has been used asmedicinal herb. Extract of Garcinia mangostana has been reported having anti-inflammatory, anti-tumour, anti-oxidant and antimicrobial activities. Bioactivecompounds from extract of mangosteen fruit husk were thought to produce byendophytic fungi. The purpose of this research were to isolate and characterizeendophytic fungi from mangosteen fruit husk that potential to produce antimicrobialcompound. Antimicrobial activity was determined by measuring the inhibition zonewith Agar Disc and Kirby-Bauer assay methods using pathogenic microbes i.e. Candidaalbicans, Staphylococcus aureus and Escherichia coli. Eleven of twenty isolatesendophytic fungi which were obtained from mangosteen fruit husk were known to haveantimicrobial activities. Endophytic fungi producing antimicrobial belongs to genusAspergillus, Penicillium, Trichoderma, Alternaria and Fusarium. Endophytic fungihaving the highest antimicrobial activities in agar disc assay were Penicilliumsp.1KMA, Aspergillus sp.5KMR, Aspergillus sp.1KMA, Fusarium sp.KMR andAspergillus sp.3KMB. Endophytic fungi having the highest antimicrobial activities inKirby-Bauer assay was Penicillium sp.1KMA. Antimicrobial activities of Penicilliumsp.1KMA was significantly different with the other four endophytic fungi.